Elizabeth A. Zachariadou, Studies in Pre-Ottoman Turkey and the Ottomans, Ashgate Variorum (Variorum Collected Studies Series), 2007, xiv+332 pages. - Σαρηγιάννης Μαρίνος (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2015)
[ Δε διατίθεται περίληψη / no abstract available]